2012
DOI: 10.1002/14651858.cd009925
|View full text |Cite
|
Sign up to set email alerts
|

Second trimester serum tests for Down's Syndrome screening

Abstract: Background Down's syndrome occurs when a person has three copies of chromosome 21-or the specific area of chromosome 21 implicated in causing Down's syndrome-rather than two. It is the commonest congenital cause of mental retardation. Noninvasive screening based on biochemical analysis of maternal serum or urine, or fetal ultrasound measurements, allows estimates of the risk of a pregnancy being a ected and provides information to guide decisions about definitive testing. Objectives To estimate and compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 460 publications
3
50
0
2
Order By: Relevance
“…In order to obtain the regressive medians of free β-HCG and AFP in Nanjing, curve regression analysis was performed, and the best curve regression equations among these were obtained. The equation for free β-HCG was y=-0.039212963x 3 (Fig. 1B, R 2 =0.999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain the regressive medians of free β-HCG and AFP in Nanjing, curve regression analysis was performed, and the best curve regression equations among these were obtained. The equation for free β-HCG was y=-0.039212963x 3 (Fig. 1B, R 2 =0.999).…”
Section: Resultsmentioning
confidence: 99%
“…The authors also reported that the detection of two or three indicators (AFP, uE3, total or free β-HCG) was better compared with that of any single indicator, and the detection rate was 60-70%, with a false-positive rate of 5%. In addition, it was demonstrated that the quadruple testing with AFP, HCG, uE3 and inhibin-A had the highest diagnostic yield, but there was no significant advantage when compared with the traditional triple test (AFP, uE3 and HCG) (3). It has been widely recognized that different serum markers, cut-off values of risks, or the determination of multiples of the median, may all affect the detection rate.…”
Section: Introductionmentioning
confidence: 99%
“…Lower sensitivity occurred in women above 35 years of age. 15 When the amniocentesis results of the patients were reviewed by Danisman N et al as numerically normal or abnormal; 40 (2.7%) of 1456 amniocentesis procedures performed for advanced maternal age, 5 (0.9%) of 531 procedures performed for an increased double-test risk and 14 (1.3%) of 1095 procedures performed for an increased triple test risk were found to have chromosomal aneuploidy. 16 Stenhouse EJ found that the detection rate for Down syndrome was 93% (14/15) at a false-positive rate of 5.9% and for all chromosome abnormalities it was 96% (25/26) at an overall false-positive rate of 6.3%.…”
Section: Resultsmentioning
confidence: 99%
“…DHEA sulfate is also converted to 16α-hydroxy DHEA sulfate in the fetal liver, via 16α-hydroxylase, and subsequently converted to estriol (>60mg/day during the third trimester of human gestation) in the placenta (Figure 3). Whilst decreased levels of estriol in maternal circulation have been used as a marker for Down and trisomy 18 syndromes, pregnancy loss, as well as gross neural tube defects such as anencephaly [78], the role of perturbed DHEA and estriol sulfonation in modifying maternal estriol levels and possibly human fetal development, awaits further investigation.…”
Section: Steroid Sulfates In Pregnancymentioning
confidence: 99%